Pilonidal sinus: why does it recur - Rahoma, Ahmed Hussein (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction: Ring formation, a structural chromosomal abnormality, is frequently observed in X chromosome. This article reports the 45,X along with 46,X, r(X) cell lines and its associations to the observed phenotypic features in an Indian female proband aged 15 years. Methods: The karyotype was determined from peripheral lymphocyte culture and Giemsa-Trypsin banding technique. Results: The karyotype was 45,X/46,X,r(X) (p11q13) (18%82%). The presence of 45,X and ring X in mosaicism status indicates that the karyotype is a Turner syndrome variant. The variably manifested phenotypic features in the proband could be due to the presence of single X, the lost segments in ring X and the mosaicism status for the X. Conclusion: During counseling, proband’s chromosomal status and its effect were explained to the proband’s parents. Parents were also counselled about the importance of medical management, education and career to the proband.